PERBANDINGAN PROFIL SENSORI TEH HIJAU MENGGUNAKAN METODE ANALISIS DESKRIPSI KUANTITATIF DAN CATA (CHECK-ALL-THAT-APPLY) - Dede Robiatul Adawiyah; Malik Abdul Azis; Amalia Shabrina Ramadhani; Piyaporn Chueamchaitrakun (Jurnal Teknologi dan Industri Pangan, 2019)
Tea is one of the most widely consumed beverages in the world. Different types of tea provide different sensory profiles. The present study aimed to evaluate sensory characteristics of green tea by analytical sensory evaluations through QDA (Quantitative Descriptive Analysis) and CATA (Check-All-That-Apply) methods. The sensory characteristics of green tea from three different countries (China, Thailand and Indonesia) were evaluated using QDA by trained panels and CATA by consumer panels. The QDA method revealed sensory characteristics of green tea, while CATA method presented information on consumer preferences towards the most desirable characteristics of green tea. The results showed that green tea has dominant characteristics of bitter taste, astringent aftertaste, green flavor, fermented flavor and dry aroma. Moreover, floral aroma and flavor in green tea have considerable influences on the panelist preferences. However, “nice to have” attribute was not found in the penalty analysis. The “must have” attribute in green tea was floral aroma, while the “must not have” attributes were burned aroma, burned flavor and dry aroma.